As the function is already given as a product, we do not need to factorize it, which is the first step to find the zeros of a function.
Now, remember that to find the zeros (also known as roots) we need to make the expression equal to 0:
![0=(x+2)(x-1)(x-3)(x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/g9vhujvghzp99cy7zqnn936yvnduiz7jgg.png)
Think about this, for the function to be equal to 0 at least one of the factors must be 0, use this information to find the zeros of the function, equal each of the factors to 0 and solve for x:
![\begin{gathered} x+2=0 \\ x=-2 \\ x-1=0 \\ x=1 \\ x-3=0 \\ x=3 \\ x+1=0 \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s9tc6v98627q2w6s76xi1qike13oy9gia9.png)
It means that the zeros of the function are -2, -1, 1, 3.
The correct answer is C.